Bipolar disorder and depression in early adulthood and long‐term employment, income, and educational attainment: A nationwide cohort study of 2, 390, 127 individuals. Issue 11 (11th September 2019) - Hakulinen, Christian; Musliner, Katherine L.; Agerbo, Esben
Abstract: Background: Mood disorders are known to be associated with poor socioeconomic outcomes, but no study has examined these associations across the entire worklife course. Our goal was to estimate the associations between bipolar disorder and depression in early adulthood and subsequent employment, income, and educational attainment. Methods: We conducted a nationwide prospective cohort study including all individuals ( n  = 2, 390, 127; 49% female) born in Denmark between 1955 and 1990. Hospital‐based diagnoses of depression and bipolar disorder before age 25 were obtained from the Danish psychiatric register. Yearly employment, earnings, and education status from ages 25 to 61 were obtained from the Danish labor market and education registers. We estimated both absolute and relative proportions. Results: Population rates of hospital‐diagnosed depression and bipolar between ages 15–25 were 1% and 0.12%, respectively. Compared to individuals without mood disorders, those with depression and particularly bipolar disorder had consistently poor socioeconomic outcomes across the entire work‐life span. For example, at age 30, 62% of bipolar and 53% of depression cases were outside the workforce compared to 19% of the general population, and 52% of bipolar and 42% of depression cases had no higher education compared to 27% of the general population. Overall, individuals with bipolar disorder or depression earned around 36% and 51%, respectively, of the income earned by individuals without mood disorders. All associations were smaller for individuals not rehospitalized after age 25. Conclusions: Severe mood disorders with onset before age 25, particularly bipolar disorder, are associated with persistent poor socioeconomic outcomes across the entire work‐life course.